2015
DOI: 10.1111/jgh.12995
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effects and autonomic mechanisms of needle‐less transcutaneous electrical stimulation atST36 on stress‐induced impairment in gastric slow waves

Abstract: Needle-less TEA at ST36 using a watch-size stimulator is able to improve stress-induced impairment in gastric slow waves, possibly mediated via the autonomic mechanism. Home-based needle-less TEA may be a viable therapy for stress-induced impairment in gastric motility functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…A number of studies using the spectral analysis of HRV to explore the autonomic mechanisms of acupuncture/EA at ST36. Most previous studies reported that the effects of acupuncture/EA on gastric dysrhythmias were mediated via the vagal mechanism . In region‐specific effects of acupuncture, Takahashi and co‐workers demonstrated that EA at ST‐36 decreased the ratio of LF/HF in normal rats, suggesting excitatory gastric responses were mediated via the vagal pathway .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies using the spectral analysis of HRV to explore the autonomic mechanisms of acupuncture/EA at ST36. Most previous studies reported that the effects of acupuncture/EA on gastric dysrhythmias were mediated via the vagal mechanism . In region‐specific effects of acupuncture, Takahashi and co‐workers demonstrated that EA at ST‐36 decreased the ratio of LF/HF in normal rats, suggesting excitatory gastric responses were mediated via the vagal pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation parameters were set as follows: a train of on‐time of 2 seconds, off‐time of 3 seconds, pulse frequency of 25 Hz, and amplitude of 4 mA. The selection of this acupoint and set of parameters were based on a few previous studies that showed enhancive effects on gastric motility . The output of 4 mA was found to be tolerable by all rats (no obvious behaviors suggesting pain or discomfort).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A watch‐size digital stimulator (SNM‐FDC01, Ningbo Maida Medical Device, Inc., Ningbo, China) was used to deliver trains of pulses. The stimulation parameters for ST36 stimulator were set at 2 sec on and 3 sec off, pulse width of 0.5 msec, pulse frequency of 25 Hz, and amplitude of 2–10 mA (at the maximum level tolerated by the subject) based on previous studies ; for PC6, stimulator was set at 0.1 sec on and 0.4 sec off, pulse width of 0.5 msec, pulse frequency of 100 Hz, and amplitude of 2–10 mA, which were shown to improve nausea and vomiting, and visceral pain . The bilateral stimulation TN treatment was given for half hour, twice daily (once on the day of surgery), lasting for 4 days.…”
Section: Methodsmentioning
confidence: 99%
“…Gastric pace‐making activity (slow waves) was assessed by a 4‐channel portable EGG recorder (MEGG‐04A, Ningbo Medkinetic, Inc., Ningbo, Zhejiang, China) . The subject was fasted for more than 6 hours and asked to lie supine.…”
Section: Methodsmentioning
confidence: 99%